2020
DOI: 10.21203/rs.2.16974/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Be Quiet and Man Up: A Qualitative Questionnaire Study into Fathers Who Witnessed Their Partner’s Birth Trauma

Abstract: Background: Research focusing on paternal mental health is limited, especially regarding the impact of the experience of poor mental health in the perinatal period. For example, little is known about the experiences of fathers who witness their partner’s traumatic birth and the subsequent impact on their mental health. Therefore, the aim of this study was to explore fathers’ experiences of witnessing a traumatic birth, how these experiences impacted their wellbeing, and what support they received during and fo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 20 publications
4
19
0
Order By: Relevance
“…Consistent with findings of spouses in other studies of obstetric emergencies, men in this study hid their feelings and reactions, believing they needed to appear strong (Daniels et al, 2020; Lindberg & Engström, 2013; Patel et al, 2019). Simmons (2019) described this as facading ; a man puts his own emotions on hold as a way of being supportive to his wife.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Consistent with findings of spouses in other studies of obstetric emergencies, men in this study hid their feelings and reactions, believing they needed to appear strong (Daniels et al, 2020; Lindberg & Engström, 2013; Patel et al, 2019). Simmons (2019) described this as facading ; a man puts his own emotions on hold as a way of being supportive to his wife.…”
Section: Discussionsupporting
confidence: 88%
“…Men's emotional distress, shock, and fears, as exposed in our study, have been documented in studies of obstetric near misses (Mbalinda et al, 2015), and studies of cesarean births with complications (Lindberg & Engström, 2013). Consistent with our participants' descriptions of being sidelined, other obstetric studies also reported men feeling ignored, secluded, isolated, uncared for, overlooked, uninformed, a spectator, abandoned, or invisible (Daniels et al, 2020; Etheridge & Slade, 2017; Hodgson et al, 2021; Lindberg & Engström, 2013; Mbalinda et al, 2015; Messner, 2018; Patel et al, 2018). Emotional distress (Patel et al, 2019) and delayed treatment because of misdiagnoses (Dekker et al, 2016; Hess & Weinland, 2012), coupled with sidelining, likely increased the uncertainty these men faced.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These researchers employed a qualitative questionnaire consisting of open-ended questions in which participants articulated how they perceived mental health, how they defined mental health, and how they understood their role in addressing mental health issues. A Qualitative questionnaire (also referred to as a qualitative survey) is an instrument comprised of open-ended questions and used to obtain information (Braun et al, 2013; Daniels et al, 2020). Researchers distributed the questionnaire ahead of time and did not restrict word count to allow participants to review questions in advance and provide more in-depth responses.…”
Section: Methodsmentioning
confidence: 99%
“…Healthcare systems such as the UK National Health Service (NHS) have primarily focused service provision on maternal mental health and wellbeing during a woman's transition into parenthood. Our recent research has con rmed that fathers feel their mental health is overlooked by perinatal health professionals [17,18].…”
Section: Introductionmentioning
confidence: 97%